Community Empowerment Through 2nd Generation Tempeh Innovation Towards a Food Organized Village - Raharjo, Sentot Joko; Fidyasari, Ambar (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
Tempeh is one of Indonesia's traditional foods. Currently proposed to be a world cultural heritage in UNESCO. Tempeh cannot last long, so it takes innovation that can increase the economic value of tempeh itself. The main objective of this empowerment program is to optimize the potential of â€œUKMâ€ (Small and Medium Industries) in the food sector for tempeh craftsmen and reduce the losses of tempeh craftsmen for those whose tempeh is not sold. The target partner of this community assistance program is the â€œUKMâ€ group Tempeh Village in Beji Village, Junrejo, Batu City who has been economically productive as Tempeh craftsmen. The method used is Asset Based Communities Development (ABCD), where the community service focuses on assets owned by the community as the main basis for program development. The efforts carried out are assistance to SMEs to deliver material on the nutritional value of 2nd generation tempeh, workshops and 2nd generation tempe making practices, entrepreneur assistance and evaluation. This innovation is expected to be a solution to the unsold tempeh problem. This assistance was carried out for 3 months. The output of this empowerment activity is in the form of material modules, 2nd generation tempeh products, understanding of the nutritional value concept of second generation tempeh and digital marketing media plans.